Entre imagens e palavras: o discurso de uma campanha de prevenção ao crack - Petuco, Dênis Roberto da Silva (2011)
Crack use is presented as one of the major social problems of contemporaneity. Aimed directly or indirectly as a cause of death of large numbers of people, especially poor young men, the crack expands greatly the vulnerability of all persons, especially young and poor man, connected with any of the stages of production, circulation, trade and consumption. Amid this problem, the prevention campaigns to drug use. The aim of this study is to contribute to the necessary reflection about the discourse in prevention campaigns to drug use. In this investigation, we analyzed the statements in the campaign Crack nem pensar , by Rede Brasil Sul de Comunicação (RBS), like other campaign, and found traces which may point out the discourse made there. To this end, we used elements of Archaeological Analysis of Discourse of Michel Foucault, and reflexive elements expressed by authors of the Philosophy of Difference, and Popular Education. Concluded that the discourse of the campaigns have as subject the user crack, registered as monstrous and dangerous figure, capable of damaging and/or make hurt the people around you.